Molecular Catalysts for Energy Conversion - Okada, Tatsuhiro (Springer, 2017)
The role of molecular catalysts for energy conversion grows more and more important since these have wide applications in fuel cells, electrochemical solar cells, artificial photo-syntheses, and so on. A firm strategy for their design and application is awaited to cope with the expeditious solution of the latest energy and environment issues. This book aims to provide the basis of molecular catalysts useful in energy conversion and environmental protection, and to establish a methods for efficient processing, manufacturing and development. This book will be beneficial for those people who are studying, researching or developing molecular catalysts in energy conversion systems.